Conservation education promotes positive short- and medium-term changes in perceptions and attitudes towards a threatened primate species - Bernárdez-Rodriguez, Galicia Fernanda; Bowler, Mark; Braga-Pereira, Franciany; McNaughton, Maxine; Mayor, Pedro (Ethnobiology and Conservation, 2021)
Many wildlife conservation projects aim to change the perceptions of local communities through conservation education programs. However, few assess whether and how these programs effectively promote shifts in community perceptions and attitudes towards wildlife conservation. We designed an educational program focused on communicating to local inhabitants from a remote community in the Peruvian Amazon that their territories are considered globally important for the red uakari (Cacajao calvus), and inspire them to become protectors and defenders of this endangered species. We aimed to evaluate changes in perceptions and attitudes towards the red uakari monkey after a conservation education workshop. We found that positive attitudes and perceptions towards the red uakari (such as uakari hunting suspension and perception of uakari importance) increased immediately after and in the short-term (two years) following the workshop but diminished in the medium-term (three years). However, attitudes remained better than before the workshop. Our results indicate that conservation education programs are useful in encouraging positive attitudes towards wildlife conservation in the short term, but ongoing environmental education activities may be necessary to have lasting positive effects.